Morocco : Financial Sector Assessment Program: Technical Note-Stress Testing the Banking System. (IMF Staff Country Reports; Country Report ;, 2016)
This Technical Note discusses the key findings of the stress testing of the banking system in Morocco. The stress tests examined the resilience of the Moroccan banking system to solvency, liquidity, and contagion risks. The global liquidity stress tests revealed that most banks in the system would be exposed to liquidity risks in the event of large deposit withdrawals, under a more severe scenario than the Basel III Liquidity Coverage Ratio metrics, or depletion of unsecured wholesale funding. Banks were found to be less vulnerable to direct contagion risk through bilateral exposure. The contagion risk analysis revealed that the risks stemming from domestic interbank exposures are very limited.